Carmen Mellado Blanco (ur.): Theorie und Praxis der idiomatischen Wörterbücher: Tübingen, 2009. Lexicographica. Series Maior; 135. VI + 255 str. - Jesenšek, Vida (Slavia Centralis, 2020)
The article describes a monograph published in the framework of the contrastive (Spanish-German) FRASESPAL project, which presents some theoretical and practical guidelines for compiling monolingual and multilingual phrase dictionaries.
Keywords: monography; Theorie und Praxis der idiomatischen Wörterbücher; project FRASESPAL; review; phrase dictionaries